More on middlemen: Equilibrium entry and efficiency in intermediated markets - Ed Nosal; Yuet-Yee Wong; Randall Wright (Federal Reserve Bank of Chicago, 2014)
This paper generalizes Rubinstein and Wolinsky's model of middlemen (intermediation) by incorporating production and search costs, plus more general matching and bargaining. This allows us to study many new issues, including entry, efficiency and dynamics. In the benchmark model, equilibrium exists uniquely, and involves production and intermediation for some parameters but not others. Sometimes intermediation is essential: the market operates iff middlemen are active. If bargaining powers are set correctly equilibrium is efficient; if not there can be too much or too little economic activity. This is novel, compared to the original Rubinstein-Wolinsky model, where equilibrium is always efficient.
Keywords: G24; D83; 330; Middlemen; Intermediation; Search; Bargaining; Entry